A MULTI-DIMENSIONAL METHOD FOR EVALUATING A PRODUCT’S CONCEPTUAL SCHEMES - Zhou, Jing; Guo, Gang; Dong, Fa Yuan; Li, Hao; Lin, Li; Yang, Fang-yan (The South African Journal of Industrial Engineering, 2014)
The use of conceptual scheme evaluation is a key step in the development of new products. In this paper, a multi-dimensional evaluation method that involves subjective evaluation, eye-tracking, and product image evaluation is established. In this study, subjective evaluation is used to test customers’ initial reactions to conceptual schemes, and eye- tracking is used to highlight the features of conceptual schemes that are most attractive to customers. With the help of Kansei engineering, the most attractive features of a particular product are described and clarified from the product image evaluation. This multi- dimensional method can be applied not only in screening conceptual schemes, but also in exploring the reasons and suggestions for product improvement. The method was assessed in this study through a case study evaluation of conceptual design schemes for a mobile phone.